PERAN KUALITAS AUDIT DAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERASI ANTARA KARAKTERISTIK KOMITE AUDIT DAN MANAJEMEN LABA - Nurmawati, Ulmi; Zaitul, Zaitul; Ilona, Desi (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Earnings management is the act of managing financial statements related to earnings over several periods. In companies, earnings management plays a very important role in maintaining the company's condition by regulating and managing its financial statements so as to increase investor confidence. The purpose of this study is to determine the effect of audit committee characteristics, such as audit committee independence, audit committee size, and audit committee expertise, on earnings management with audit quality and financial performance as moderating variables in the building construction sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Based on the selected sample criteria, there were 80 observations and 20 company samples to fulfill the research objectives. Discretionary accruals were used as a proxy to assess earnings management. The results of the study indicate that the independence of the audit committee affects earnings management. Meanwhile, the size and expertise of the audit committee do not affect earnings management. The interaction variable results show that audit quality can moderate the effect of audit committee independence on earnings management, and audit quality can moderate the effect of audit committee size on earnings management.